2017
DOI: 10.1016/j.celrep.2017.10.087
|View full text |Cite
|
Sign up to set email alerts
|

Mucus Detachment by Host Metalloprotease Meprin β Requires Shedding of Its Inactive Pro-form, which Is Abrogated by the Pathogenic Protease RgpB

Abstract: The host metalloprotease meprin β is required for mucin 2 (MUC2) cleavage, which drives intestinal mucus detachment and prevents bacterial overgrowth. To gain access to the cleavage site in MUC2, meprin β must be proteolytically shed from epithelial cells. Hence, regulation of meprin β shedding and activation is important for physiological and pathophysiological conditions. Here, we demonstrate that meprin β activation and shedding are mutually exclusive events. Employing ex vivo small intestinal organoid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 61 publications
6
60
0
Order By: Relevance
“…For instance, binding of BACE1 to the adaptor protein GGA promotes degradation (Tesco et al , ) and this is blocked by a specific sugar modification, bisecting N‐acetylglucosamine (Kizuka et al , ). As an alternative to lysosomal degradation, classical sheddases may be shed themselves, e.g., ADAM10, BACE1, and meprin β (Hussain et al , ; Tousseyn et al , ), which may be considered a mechanism for inactivating a sheddase (Wichert et al , ).…”
Section: Regulation Of Sheddingmentioning
confidence: 99%
“…For instance, binding of BACE1 to the adaptor protein GGA promotes degradation (Tesco et al , ) and this is blocked by a specific sugar modification, bisecting N‐acetylglucosamine (Kizuka et al , ). As an alternative to lysosomal degradation, classical sheddases may be shed themselves, e.g., ADAM10, BACE1, and meprin β (Hussain et al , ; Tousseyn et al , ), which may be considered a mechanism for inactivating a sheddase (Wichert et al , ).…”
Section: Regulation Of Sheddingmentioning
confidence: 99%
“…7). Besides ADAM10‐ and ADAM17‐mediated shedding of inactive promeprin β (8), we revealed that meprin β can boost the activity of ADAM proteases 9, 10, and 17. Virulence factors, such as RgpB, can activate membrane‐bound meprin β, thereby leading to pathologic conditions by changing its substrate repertoire as previously shown for the intestine (8).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that meprin β activation and its shedding by ADAM10 and 17 are mutually exclusive events (8). This strict regulation of meprin β activity can be overridden by bacterial pathogens as demonstrated for the bacterial protease Arg‐ RgpB, which causes severe inflammation in the intestine (8). On the other hand, meprin β was shown to induce the production of proinflammatory cytokines in macrophages, including IL‐1b and IL‐18 (47, 48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meprin a is shed by furin on the secretory pathway, oligomerized, and secreted into the extracellular space (1,2). Meprin b, on the other hand, stays at the cell membrane until it is shed by a disintegrin and metalloproteases (ADAMs) to reach a different subset of substrates (3,4). Shortly after discovery of meprins, it was shown that both proteases form heterodimers in mice and rats when coexpressed (1,5).…”
mentioning
confidence: 99%